Fires in the Amazon Region: Quick Policy Review - Luca Eufemia; Ana Paula Dias Turetta; Michelle Bonatti; Emmanuel Da Ponte; Stefan Sieber (Development Policy Review, 2022)
Motivation The combination of institutional weaknesses, climate change, and overexploitation is increasingly recognized as endangering the Amazon forest. These three factors made 2020 the worst year for forest fires recorded in the previous 600.167emyears. We analyse environmental policies across the nine countries of the Amazon Basin to develop national and regional forest programmes to tackle this scenario. Purpose The study synthesizes and compares key environmental legislation concerning protected natural areas (PNAs) and fire management in the nine countries of the Amazon Basin. To this end, the research question asks what directions can be drawn from a visualization and compilation of national regulations for future policy research and practice. Methods and approach We undertake a critical literature review of PNAs and fire-management policies across the nine countries of the Amazon Basin and their further alignment using analyses of previous policy reviews on forest codes and land distribution. Findings The article shows the heterogeneity of national fire-use and fire-management policies among the nine countries of the Amazon Basin. In addition, it suggests that top-down policies and regulations are likely to be characterized by misunderstandings (either direct or indirect) of local practice, rationale, and capacity; and, in some cases, risk criminalizing local and indigenous daily subsistence. Policy implications The study indicates the need for more in-depth research and policy on participatory governance platforms for the use and management of fire, rather than fire-suppression and fire-risk adaptation strategies. There are some positive, albeit often isolated, cases, to which scholars, policy-makers, and environmental practitioners should pay more attention.
Keywords: 300; Amazon Basin; fire governance; forest policies; land-use policies; management policies; wildfire policies